The Dynamic Analysis of Piping Systems using Pseudo-Dynamic Techniques - F. J. M. Q. de Melo (2001)
This paper describes an application of pseudo-dynamic techniques to the dynamic analysis of piping structures. Essentially it consists in coupling a direct time integration algorithm, such as the Newmark method, to an experimental step. At each time step the integration algorithm generates a displacement vector of the structure, which is prescribed for the test specimen. This is mounted in a rigid test rig fitted with a set of displacement actuators and load cells at the level of the structure degrees of freedom. The load cells allow the reading of the internal restoring force vector, which is fed back to the direct time integration algorithm in an actual time step. Further calculations for the velocity and acceleration vectors will define a new structure configuration by evaluating a new displacement vector referred to the next time step. This procedure makes it possible to assess experimentally a realistic stress distribution at sections of complex shape piping parts. The method is a precise tool in dynamic analysis and, on being carried out in a quasi-static procedure, it operates with less expensive equipment than is necessary in real dynamic test.